Cylindrical lithium ion battery, preparation method thereof and power utilization device comprising cylindrical lithium ion battery

By using negative electrode active coating with a silicon content of 2 to 30% and secondary cold pressing process in the negative electrode sheet of lithium ion cylindrical battery, the cracking of active particles and pore structure damage caused by the cold pressing method of negative electrode sheet of traditional lithium ion cylindrical battery is solved, and the electrochemical performance, safety performance and low-temperature energy release rate are improved.

CN119864489APending Publication Date: 2025-04-22JIANGSU RELIANCE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510236191.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The single cold pressing method of the negative electrode sheet of the traditional lithium-ion cylindrical battery leads to the breakage of active particles and the damage to the pore structure, resulting in the blockage of the lithium-ion transmission channel, poor negative electrode dynamics, low rate performance and low temperature energy release rate, and also affected the cycle performance and safety performance.

Method used

By optimizing the design of the negative electrode sheet, an active negative electrode coating with a silicon content of 2 to 30%, and a secondary cold pressing processing technology is adopted to regulate the pore structure of the high-silicon negative electrode sheet, reduce pore blockage, reduce pore impedance and pore tortuousness, and improve the lithium kinetics of the negative electrode deintercalation.

Benefits of technology

It improves the electrochemical performance and safety performance of lithium-ion cylindrical batteries, improves the low-temperature energy release rate, improves the cycle stability and safety performance of the battery, and realizes the wide temperature domain application of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864489A_ABST
    Figure CN119864489A_ABST
Patent Text Reader

Abstract

The invention provides a cylindrical lithium ion battery, a preparation method thereof and an electric device comprising the cylindrical lithium ion battery, and relates to the technical field of lithium ion batteries. According to the cylindrical lithium ion battery disclosed by the invention, through formula design of the negative plate with the silicon content of 2-30wt% and a secondary cold pressing processing technology, the pore structure of the high-silicon negative plate can be effectively regulated and controlled, the blockage phenomenon of negative pores is reduced, the rate performance of the cylindrical battery is improved, and the low-temperature energy release condition of the battery is further improved. Meanwhile, according to the negative electrode formula design and the secondary cold pressing mode, the particle breaking condition of the high-silicon negative electrode plate can be improved, generation of a new interface in the cold pressing stage of the electrode plate is reduced, and the thermal stability and the electrochemical stability are improved. Therefore, the electrochemical performance, the safety performance and the low-temperature energy release rate of the lithium ion cylindrical battery can be effectively improved, and the lithium ion cylindrical battery is of great significance to wide-temperature-range application of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion cylindrical battery and a preparation method thereof, and an electric device comprising the same. Background Art

[0002] As a widely used energy storage device in recent years, lithium-ion batteries can provide energy support for many products such as electric vehicles, consumer electronics, and power tools, showing huge market prospects. With the current development of lithium batteries, the market has put forward higher requirements for energy density, charge and discharge rate, and application environment (temperature, humidity, vibration and shock, etc.). Among them, the wide temperature range application of batteries is one of the biggest challenges. In low temperature environments, it is difficult to fully utilize the battery capacity due to the influence of lithium ion migration kinetics and lithium deintercalation reaction thermodynamics.

[0003] Cylindrical batteries are favored by the market due to their high energy density, excellent rate performance, mature production process and good consistency. However, the single cold pressing method of the negative electrode of the traditional lithium-ion cylindrical battery has relatively harsh cold pressing conditions, that is, the cold pressing pressure is higher and the roller gap is smaller, the active particles are broken and block the pores, causing the negative electrode pore structure to be destroyed, the lithium ion transmission channel is blocked and the path is longer, and the pore impedance is very high. Therefore, the negative electrode kinetics is poor, the cylindrical battery rate performance is poor, and the low-temperature energy release rate is very low; in addition, the negative electrode active particles are broken, the active specific surface area increases, and the side reactions consume more active lithium, the battery first efficiency is reduced, the cycle performance deteriorates, and the thermal stability and electrochemical stability are seriously deteriorated.

[0004] Therefore, it is of great significance to study and develop a new negative electrode plate for lithium-ion cylindrical batteries and a preparation method thereof, improve the negative electrode dynamics of lithium-ion cylindrical batteries, increase the low-temperature energy release rate of the battery, improve the cycle stability and safety performance of the battery, and realize the wide temperature range application of lithium-ion batteries.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The first object of the present invention is to provide a lithium-ion cylindrical battery, which effectively improves the electrochemical performance and safety performance of the lithium-ion cylindrical battery, as well as the low-temperature energy release rate, by optimizing the design of the negative electrode plate.

[0007] The second object of the present invention is to provide a method for preparing a lithium-ion cylindrical battery.

[0008] The third object of the present invention is to provide an electrical device comprising the above-mentioned lithium-ion cylindrical battery.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] A cylindrical lithium-ion battery provided by the present invention includes a housing, a cylindrical wound core located inside the housing, and an electrolyte. The cylindrical wound core is wound by a positive electrode sheet, a negative electrode sheet, and a separator therebetween;

[0011] Wherein: The preparation method of the negative electrode sheet includes: providing a negative electrode current collector, applying a negative electrode active paste on the negative electrode current collector and drying to obtain a negative electrode active coating, and then obtaining the negative electrode sheet through secondary cold pressing and slitting; the mass fraction of silicon in the negative electrode active coating is 2-30%.

[0012] Preferably, the mass fraction of silicon in the negative electrode active coating is 2-10%.

[0013] Furthermore, the target compaction density of the secondary cold pressing is a, the compaction density of the negative electrode sheet coating before cold pressing is b, the ratio of the first cold pressing is c, and the compaction density after the first cold pressing is e, then e = b + (a - b)·c;

[0014] Wherein: the target compaction density a of the secondary cold pressing is 1.2 g / cc ≤ a ≤ 1.8 g / cc, the compaction density b before cold pressing is 0.1 g / cc < b < 1.8 g / cc and b < a, and the ratio c of the first cold pressing is 0.5 ≤ c ≤ 0.9.

[0015] Furthermore, the pore impedance R of the negative electrode sheet satisfies R0·c·e x+(a-1) ≤ R ≤ R0·e x+(a-1) , where R0 is the pore impedance of the negative electrode sheet when a = 1, c = 1, and x = 2%, and satisfies 0.1 Ω·cm 2 < R0 < 100 Ω·cm 2 ; wherein: a is the target compaction density of the secondary cold pressing, c is the ratio of the first cold pressing, and x is the mass fraction of silicon in the negative electrode active coating;

[0016] And / or, the double-layer capacitance value Cdl of the negative electrode sheet satisfies Cdl0 ≤ Cdl ≤ Cdl0(1 + c) x+(a-1) , where Cdl0 is the double-layer capacitance value when a = 1, c = 1, and x = 2%, and satisfies 1.00×10 -05 F / cm 2 < Cdl0 < 1.00×10 -02 F / cm 2 ; wherein: a is the target compaction density of the secondary cold pressing, c is the ratio of the first cold pressing, and x is the mass fraction of silicon in the negative electrode active coating.

[0017] Furthermore, the crushing rate ρ of the silicon particles of the negative electrode sheet after cold pressing satisfies ρ0·c·(1 + x) 2 ≤ ρ ≤ ρ0·(a + x) 2,ρ0 is a=1,c=1,x=2%, the crushing rate of silicon particles satisfies 0≤ρ0<20%.

[0018] Where: a is the target compaction density of the secondary cold pressing, c is the ratio of the first cold pressing, and x is the mass fraction of silicon in the negative electrode active coating.

[0019] Furthermore, the absolute value of the overpotential ηV and the temperature T℃ during the discharge process of the cylindrical battery satisfy: 0≤η≤1.3+e -(T / 10+4) , the discharge interval of the overpotential η is 0 to 10% DOD.

[0020] Furthermore, the negative electrode active coating includes at least two of a negative electrode active material, a conductive agent, a binder and a dispersant.

[0021] Furthermore, the negative electrode active material includes at least two or a combination of two or more of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-carbon material, silicon-oxygen material and silicon-based alloy.

[0022] Furthermore, the diameter of the lithium-ion cylindrical battery is 20 to 50 mm, and the height is 50 to 150 mm.

[0023] The present invention provides a method for preparing a lithium-ion cylindrical battery, the method comprising:

[0024] (A) preparing a negative electrode: adding a negative electrode active material, a conductive agent, a binder and a dispersant into a solvent to form a mixed dispersion A to obtain a negative electrode active slurry; then coating the negative electrode active slurry on at least one side of a current collector, and drying to form a negative electrode active coating; then performing secondary cold pressing and slitting to obtain a negative electrode sheet;

[0025] Preferably, the mass ratio of the negative electrode active material, the conductive agent, the binder and the dispersant is 85-99.8:0.1-5:0.1-5:0-5;

[0026] The negative electrode active material, conductive agent, binder and dispersant in the mixed dispersion A are solutes;

[0027] Preferably, the mass ratio of the solvent to the solute in the mixed dispersion A is 0.25 to 4:1;

[0028] Preferably, the solid content of the negative electrode active slurry is 20-80%;

[0029] (B) preparing a positive electrode: adding a positive electrode active material, a conductive agent, a binder and a dispersant into an organic solvent NMP to form a mixed dispersion B to obtain a positive electrode active slurry; then coating the positive electrode active slurry on at least one side of a current collector, and drying to form a positive electrode active coating; then cold pressing and slitting to obtain a positive electrode sheet;

[0030] Preferably, the mass ratio of the positive electrode active material, the conductive agent, the binder and the dispersant is 85-99.8:0.1-5:0.1-5:0-5;

[0031] The positive electrode active material, conductive agent, binder and dispersant in the mixed dispersion B are solutes;

[0032] Preferably, the mass ratio of the organic solvent NMP to the solute in the mixed dispersion B is 0.25 to 1.5:1;

[0033] Preferably, the solid content of the positive electrode active slurry is 40-80%;

[0034] (C) Assembling cylindrical batteries: Winding the negative electrode sheet, the positive electrode sheet and the separator together to form a battery core, welding the tabs of the battery core to the electrical connection sheet and then placing them into a shell, injecting electrolyte, sealing and forming, to obtain the lithium-ion cylindrical battery.

[0035] The present invention provides an electrical device, which includes the above-mentioned lithium-ion cylindrical battery, and the lithium-ion cylindrical battery is used to supply power to the electrical device.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The lithium-ion cylindrical battery of the present application effectively optimizes the design of the negative electrode sheet through the formula design of the negative electrode sheet (silicon content 2-30%) and the secondary cold pressing processing technology, thereby improving the electrochemical performance and safety performance of the lithium-ion cylindrical battery, as well as the low-temperature energy release rate, specifically:

[0038] (1) Low-temperature energy release performance: Through the negative electrode formula design with a silicon content of 2 to 30% and the secondary cold pressing method, the pore structure of the high-silicon negative electrode plate is regulated to reduce the negative electrode pore blocking phenomenon, reduce the pore impedance and pore tortuosity, improve the negative electrode lithium insertion and extraction kinetics, improve the cylindrical battery rate performance, and improve the low-temperature energy release of the battery.

[0039] (2) Electrochemical performance: The negative electrode formula design with a silicon content of 2 to 30% and the secondary cold pressing method can effectively improve the breakage of high-silicon negative electrode particles, reduce the formation of new interfaces during the cold pressing stage of the electrode, reduce the consumption of active lithium, and improve the initial efficiency and cycle performance of the entire battery.

[0040] (3) Safety performance: The above-mentioned negative electrode formula design with a silicon content of 2 to 30% and the secondary cold pressing method can improve the breakage of high-silicon negative electrode sheet particles, reduce the formation of new interfaces during the cold pressing stage of the electrode sheet, reduce the occurrence of side reactions on the negative electrode side, and improve thermal stability and electrochemical stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0042] Figure 1 This is a schematic diagram of the assembly of a lithium-ion cylindrical battery provided in Example 1 of the present invention;

[0043] Figure 2 A schematic diagram of the structure of the positive electrode sheet provided in Example 1 of the present invention;

[0044] Figure 3 A schematic diagram of the structure of the negative electrode sheet provided in Example 1 of the present invention;

[0045] Figure 4 This is a comparison chart of the 10C discharge capacity cycles of the lithium-ion cylindrical batteries of Example 1 and Comparative Example 3 provided in Test Example 1 of the present invention.

[0046] Icon: 1-shell; 2-positive terminal; 3-negative terminal; 4-positive column; 5-positive uncoated area; 6-ceramic coating area; 7-positive coating area; 8-negative coating area; 9-negative uncoated area. DETAILED DESCRIPTION

[0047] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] According to one aspect of the present invention, a lithium-ion cylindrical battery comprises a housing 1, a cylindrical winding core located in the housing 1, and an electrolyte, wherein the cylindrical winding core is wound by a positive electrode sheet, a negative electrode sheet, and a separator therebetween;

[0049] The preparation method of the negative electrode sheet comprises: providing a negative electrode current collector, applying a negative electrode active slurry to the current collector and drying to obtain a negative electrode active coating, and then performing secondary cold pressing and slitting to obtain a negative electrode sheet; the mass fraction of silicon in the negative electrode active coating is 2-30%.

[0050] The lithium-ion cylindrical battery provided by the present invention, the preparation method of the negative electrode sheet of the lithium-ion cylindrical battery includes: providing a negative electrode current collector, applying a negative electrode active slurry to the current collector and drying to obtain a negative electrode active coating, and then obtaining a negative electrode sheet through secondary cold pressing and slitting; the mass fraction of silicon in the negative electrode active coating is 2 to 30%. The above-mentioned lithium-ion cylindrical battery of the present invention can effectively regulate the pore structure of the high-silicon negative electrode sheet through the negative electrode formula design (silicon content) and the secondary cold pressing method, reduce the negative electrode pore blocking phenomenon, reduce the pore impedance and pore tortuosity, improve the negative electrode lithium deintercalation dynamics, improve the cylindrical battery rate performance, and improve the low-temperature energy release of the battery. At the same time, the secondary cold pressing method can effectively improve the crushing of high-silicon negative electrode sheet particles, reduce the generation of new interfaces in the cold pressing stage of the electrode sheet, reduce the consumption of active lithium and the occurrence of negative electrode side reactions, and improve thermal stability and electrochemical stability.

[0051] It should be noted that the mass fraction of silicon in the negative electrode active coating of the present application may be but is not limited to 2%, 5%, 10%, 15%, 20%, 25% or 30%, and may also be any value between 2% and 30%.

[0052] Preferably, the mass fraction of silicon in the negative electrode active coating is 2-10%.

[0053] The discharge characteristics of the lithium-ion cylindrical battery prepared by the negative electrode formula design (silicon content 2-30%) and secondary cold pressing of the present invention are as follows:

[0054] The electrochemical device with 100% SOC is placed at an ambient temperature of 25° C. for more than 6 hours, and then a discharge operation is performed at a discharge rate of 0.1C until the voltage of the electrochemical device decreases to 2.5V. The discharge capacity of the electrochemical device in the constant current discharge operation is Q1;

[0055] The electrochemical device with 100% SOC is placed at an ambient temperature T for more than 6 hours, and at the ambient temperature T, the electrochemical device is discharged at a discharge rate of K, and the discharge operation is continued until the voltage of the electrochemical device decreases to 1.5V or the device temperature increases to 65°C. The discharge capacity of the electrochemical device in the constant current discharge operation is Q2;

[0056] Wherein, the ambient temperature T satisfies -40°C≤T≤0, the discharge rate K satisfies K≥8C, and the discharge capacity satisfies Q2 / Q1≥80%.

[0057] It should be noted that the lithium-ion cylindrical battery described in the present invention includes a housing 1, an electrode assembly accommodated in the housing 1, and an electrolyte; the electrode assembly is formed by winding strip-shaped positive and negative electrode sheets via a separator layer. The strip-shaped positive electrode foil has a positive electrode active material layer and an empty foil area covered thereon, and the strip-shaped negative electrode foil also has a negative electrode active material layer and an empty foil area covered thereon. The empty foil areas of the positive and negative electrode sheets are perpendicular to the winding direction, and the top end face or the bottom end face is formed by methods such as flattening or cutting and laminating.

[0058] In a preferred embodiment of the present invention, the target compaction density of the secondary cold pressing is a, the compaction density of the negative electrode sheet coating before cold pressing is b, the ratio of the first cold pressing is c, and the compaction density after the first cold pressing is e. Then, e = b + (a - b)·c;

[0059] Wherein: the target compaction density a of the secondary cold pressing is 1.2 ≤ a ≤ 1.8 g / cc, the compaction density b before cold pressing is 0.1 g / cc < b < 1.8 g / cc and b < a, and the ratio c of the first cold pressing is 0.5 ≤ c ≤ 0.9.

[0060] It should be noted that the target compaction density a of the secondary cold pressing can be, but is not limited to, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, or 1.8, or any value between 1.2 and 1.8; the ratio c of the first cold pressing can be, but is not limited to, 0.5, 0.6, 0.7, 0.8, or 0.9, or any proportion between 0.5 and 0.9.

[0061] In a preferred embodiment of the present invention, after the secondary cold pressing treatment, the pore impedance R of the negative electrode sheet satisfies R0·c·e x+(a-1) ≤ R ≤ R0·e x+(a-1) , where R0 is the pore impedance of the negative electrode sheet when a = 1, c = 1, and x = 2%, and 0.1 Ω·cm 2 < R0 < 100 Ω·cm 2 ; wherein: a is the target compaction density of the secondary cold pressing, c is the ratio of the first cold pressing, and x is the mass fraction of silicon in the negative electrode active coating.

[0062] In a preferred embodiment of the present invention, after the secondary cold pressing treatment, the double-layer capacitance value Cdl of the negative electrode sheet satisfies Cdl0 ≤ Cdl ≤ Cdl0(1 + c) x+(a-1) , where Cdl0 is the double-layer capacitance value when a = 1, c = 1, and x = 2%, and 1.00×10 -05 F / cm 2 < Cdl0 < 1.00×10 -02 F / cm 2; Wherein: a is the target compaction density of the secondary cold pressing, c is the ratio of the first cold pressing, and x is the mass fraction of silicon in the negative electrode active coating.

[0063] In a preferred embodiment of the present invention, the crushing rate ρ of the silicon particles of the negative electrode sheet after the secondary cold pressing process satisfies ρ0·c·(1+x) 2 ≤ρ≤ρ0·(a+x) 2 ,ρ0 is the crushing rate of silicon particles when a=1, c=1, x=2%, satisfying 0≤ρ0<20%; where: a is the target compaction density of the secondary cold pressing, c is the ratio of the first cold pressing, and x is the mass fraction of silicon in the negative electrode active coating.

[0064] In a preferred embodiment of the present invention, the absolute value of the overpotential η and the temperature T during the discharge of the cylindrical battery satisfy: 0≤η≤1.3+e -(T / 10+4) , the discharge interval of the overpotential η is 0 to 10% DOD.

[0065] In a preferred embodiment of the present invention, the negative electrode active coating comprises at least two of a negative electrode active material, a conductive agent, a binder and a dispersant.

[0066] In the above preferred embodiment, the negative electrode active material includes at least two or a combination of two or more of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-carbon material, silicon-oxygen material and silicon-based alloy, and the mass fraction of silicon element in the negative electrode coating is 2 to 30%.

[0067] In a preferred embodiment of the present invention, the positive electrode sheet comprises a positive electrode current collector and a positive electrode coating coated on at least one surface of the positive electrode current collector, and the positive electrode active material in the positive electrode coating comprises a combination of at least one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel manganese oxide, lithium iron phosphate and lithium manganese iron phosphate;

[0068] In a preferred embodiment of the present invention, the diameter of the lithium-ion cylindrical battery is 20-50 mm and the height is 50-150 mm.

[0069] According to one aspect of the present invention, a method for preparing a lithium-ion cylindrical battery comprises:

[0070] (A) preparing a negative electrode: adding a negative electrode active material, a conductive agent, a binder and a dispersant into a solvent to form a mixed dispersion A to obtain a negative electrode active slurry; then coating the negative electrode active slurry on at least one side of a current collector, and drying to form a negative electrode active coating; then performing secondary cold pressing and slitting to obtain a negative electrode sheet;

[0071] Preferably, the mass ratio of the negative electrode active material, the conductive agent, the binder and the dispersant is 85-99.8:0.1-5:0.1-5:0-5;

[0072] The negative electrode active material, conductive agent, binder and dispersant in the mixed dispersion A are solutes;

[0073] Preferably, the mass ratio of the solvent to the solute in the mixed dispersion A is 0.25 to 4:1;

[0074] Preferably, the solid content of the negative electrode active slurry is 20-80%;

[0075] (B) preparing a positive electrode: adding a positive electrode active material, a conductive agent, a binder and a dispersant into an organic solvent NMP to form a mixed dispersion B to obtain a positive electrode active slurry; then coating the positive electrode active slurry on at least one side of a current collector, and drying to form a positive electrode active coating; then cold pressing and slitting to obtain a positive electrode sheet;

[0076] Preferably, the mass ratio of the positive electrode active material, the conductive agent, the binder and the dispersant is 85-99.8:0.1-5:0.1-5:0-5;

[0077] The positive electrode active material, conductive agent, binder and dispersant in the mixed dispersion B are solutes;

[0078] Preferably, the mass ratio of the organic solvent NMP to the solute in the mixed dispersion B is 0.25 to 1.5:1;

[0079] Preferably, the solid content of the positive electrode active slurry is 40-80%;

[0080] (C) Assembling cylindrical batteries: The negative electrode sheet, the positive electrode sheet and the separator are wound together to form a battery core, the tabs of the battery core are welded to the electrical connection sheet and then loaded into the housing 1, and the electrolyte is injected, and the battery core is sealed and formed to obtain the lithium-ion cylindrical battery.

[0081] Preferably, the step (B) comprises: winding the positive electrode sheet, the separator and the negative electrode sheet together to form a winding core, the edges of the positive and negative electrodes are provided with empty foil areas, one end of the cylindrical winding core is connected to the negative electrode bus bar by welding, the negative electrode bus bar is connected to the outer shell by welding, the other end of the cylindrical winding core is connected to the positive electrode bus bar by welding, an insulating sheet is placed on the positive electrode bus bar, the positive electrode bus bar is connected to the cap by welding, and then the electrolyte is injected, and finally the groove is rolled and sealed to obtain a lithium-ion cylindrical battery.

[0082] The preparation method of the lithium-ion cylindrical battery of the present invention first uses a negative electrode active slurry with a silicon content of 2 to 30% to prepare a negative electrode sheet by secondary cold pressing, and then winds the negative electrode sheet together with a positive electrode sheet and a separator to form a battery roll core, and assembles to obtain a lithium-ion cylindrical battery. The lithium-ion cylindrical battery obtained by the above preparation method of the present invention has better electrochemical performance, safety performance and low-temperature energy release efficiency.

[0083] According to one aspect of the present invention, an electrical device comprises the above-mentioned lithium-ion cylindrical battery.

[0084] The present invention provides an electrical device, which includes the above-mentioned lithium ion cylindrical battery, and the lithium ion cylindrical battery can be used to supply power to the electrical device.

[0085] The technical solution of the present invention will be further described below in conjunction with embodiments.

[0086] The test battery preparation method and steps in the following embodiments of the present application can be referred to as follows:

[0087] 1. Homogenization: The positive electrode material (such as lithium nickel cobalt aluminum oxide, conductive carbon black, binder PVDF, solvent NMP) and the negative electrode material (such as artificial graphite, conductive carbon black, single-walled carbon nanotubes, binder CMC, binder SBR, solvent deionized water) are weighed and mixed in a certain proportion to make positive or negative electrode slurry.

[0088] 2. Coating and rolling: Coat the positive electrode slurry on aluminum foil with a thickness of 12±1 microns, and coat the negative electrode slurry on copper foil with a thickness of 6±1 microns. The electrode is baked in a blast oven to remove the solvent, and then the dried electrode is rolled and cut.

[0089] 3. Winding: Align the baked positive and negative electrode sheets parallel to the diaphragm, place them on a fully automatic winding machine, and wind them to obtain a winding core.

[0090] 4. Cell assembly: Weld the positive busbar and negative busbar to the winding core respectively, then weld the negative busbar to the steel shell, place an insulating sheet on top of the positive busbar, and weld the positive busbar to the cap.

[0091] 5. Liquid injection and sealing: The electrolyte is injected by vacuum injection. The electrolyte is 1 mol / L LiPF6 electrolyte (the solvent is EC+DMC+DEC), and then the cylindrical battery is obtained by sealing.

[0092] Example 1

[0093] Figure 1 This is a schematic diagram of the assembly of a lithium-ion cylindrical battery provided in Example 1 of the present invention. Figure 1It includes a shell 1; a positive terminal 2; a negative terminal 3; and a positive pole 4.

[0094] A lithium ion cylindrical battery, wherein the preparation method of the lithium ion cylindrical battery comprises:

[0095] (1) Preparation of positive electrode sheet: Nickel cobalt aluminum lithium (NCA88), conductive carbon black, and binder PVDF were weighed and mixed in a ratio of 96:2:2, and then NMP was added to adjust the solid content of the slurry to 60%, and then coated on aluminum foil, dried, rolled and cut to obtain the following Figure 2 The positive electrode is shown.

[0096] Figure 2 This is a schematic diagram of the structure of the positive electrode sheet provided in Example 1 of the present invention. Figure 2 The reference numerals in the figures are positive electrode uncoated area 5 ; ceramic coating area 6 ; positive electrode coating area 7 .

[0097] (2) Preparation of negative electrode sheet: artificial graphite, silicon carbon, conductive carbon black, single-walled carbon nanotubes, binder CMC, and binder SBR are weighed and mixed in a ratio of 70:25:1:0.5:1.5:2 and slurried (silicon content 25%), then deionized water is added to adjust the slurry solid content to 40%, and then coated on copper foil and dried to obtain a non-cold-pressed negative electrode sheet, and then the negative electrode sheet is cold-pressed and cut according to the cold-pressing ratio (the first cold-pressing ratio in this embodiment is 70%) to obtain the following: Figure 3 The negative electrode is shown.

[0098] Figure 3 This is a schematic diagram of the structure of the negative electrode sheet provided in Example 1 of the present invention. Figure 3 The reference numerals in the figures indicate a negative electrode coated area 8 and a negative electrode uncoated area 9 .

[0099] (3) Battery assembly: The positive electrode sheet, negative electrode sheet and separator are wound by a winding machine to form a winding core, in which the positive and negative electrode sheets are provided with non-coating areas, and this part is used as positive and negative electrode ears. The winding core is cut and stacked for the positive and negative electrode ears, and then the positive busbar and negative busbar are welded to the winding core respectively, and then the negative busbar is welded to the steel shell, and an insulating sheet is placed on top of the positive busbar, and the positive busbar is welded to the cap. Then the grooving, liquid injection, sealing and formation are completed to obtain a cylindrical battery.

[0100] The relevant parameters of this embodiment are shown in Table 1 below.

[0101] Table 1 Lithium-ion cylindrical battery parameters of Example 1

[0102]

[0103]

[0104] Example 2

[0105] This embodiment is the same as Embodiment 1 except that the silicon content in the mixed slurry in step (2) is 2%.

[0106] Specifically, in the present application, artificial graphite, silicon carbon, conductive carbon black, single-walled carbon nanotubes, binder CMC, and binder SBR are weighed in a ratio of 93:2:1:0.5:1.5:2 and mixed to form a homogenous slurry (silicon content 2%).

[0107] Example 3

[0108] This embodiment is the same as Embodiment 1 except that the silicon content in the mixed slurry in step (2) is 5%.

[0109] Specifically, in the present application, artificial graphite, silicon carbon, conductive carbon black, single-walled carbon nanotubes, binder CMC, and binder SBR are weighed in a ratio of 90:5:1:0.5:1.5:2 and mixed to form a homogenous slurry (silicon content 5%).

[0110] Example 4

[0111] This embodiment is the same as Embodiment 1 except that the silicon content in the mixed slurry in step (2) is 20%.

[0112] Specifically, in the present application, artificial graphite, silicon carbon, conductive carbon black, single-walled carbon nanotubes, binder CMC, and binder SBR are weighed in a ratio of 75:20:1:0.5:1.5:2 and mixed to form a homogenous slurry (silicon content 20%).

[0113] Example 5

[0114] This embodiment is the same as Embodiment 1 except that the silicon content in the mixed slurry in step (2) is 30%.

[0115] Specifically, in the present application, artificial graphite, silicon carbon, conductive carbon black, single-walled carbon nanotubes, binder CMC, and binder SBR are weighed in a ratio of 65:30:1:0.5:1.5:2 and mixed to form a homogenous slurry (silicon content 30%).

[0116] Example 6

[0117] This embodiment is the same as Embodiment 1 except that the compaction density of the negative electrode in Table 1 is 1.2 g / cc.

[0118] Example 7

[0119] This embodiment is the same as Embodiment 1 except that the compaction density of the negative electrode in Table 1 is 1.4 g / cc.

[0120] Example 8

[0121] This embodiment is the same as Example 1 except that the compaction density of the negative electrode in Table 1 is 1.6 g / cc.

[0122] Example 9

[0123] This embodiment is the same as Embodiment 1 except that the ratio of the first cold pressing in step (2) is 90%.

[0124] Example 10

[0125] This embodiment is the same as Embodiment 1 except that the ratio of the first cold pressing in step (2) is 80%.

[0126] Embodiment 11

[0127] This embodiment is the same as Embodiment 1 except that the ratio of the first cold pressing in step (2) is 60%.

[0128] Example 12

[0129] This embodiment is the same as Embodiment 1 except that the ratio of the first cold pressing in step (2) is 50%.

[0130] Embodiment 13

[0131] This embodiment is the same as Embodiment 1 except that the battery discharge environment temperature in Table 1 is 0°C.

[0132] Embodiment 14

[0133] This embodiment is the same as Embodiment 1 except that the battery discharge environment temperature in Table 1 is -10°C.

[0134] Embodiment 15

[0135] This embodiment is the same as Embodiment 1 except that the battery discharge environment temperature in Table 1 is -20°C.

[0136] Example 16

[0137] This embodiment is the same as Embodiment 1 except that the battery discharge environment temperature in Table 1 is -30°C.

[0138] Embodiment 17

[0139] This embodiment is the same as Embodiment 1 except that the battery discharge rate in Table 1 is 8C.

[0140] Embodiment 18

[0141] This embodiment is the same as Embodiment 1 except that the battery discharge rate in Table 1 is 8C.

[0142] Embodiment 19

[0143] This embodiment is the same as Embodiment 1 except that the battery discharge rate in Table 1 is 8C.

[0144] Comparative Example 1

[0145] This embodiment is the same as Embodiment 1 except that the silicon content in the mixed slurry in step (2) is 40%.

[0146] Specifically, in the present application, artificial graphite, silicon carbon, conductive carbon black, single-walled carbon nanotubes, binder CMC, and binder SBR are weighed in a ratio of 55:40:1:0.5:1.5:2 and mixed to form a homogenous slurry (silicon content 40%).

[0147] Comparative Example 2

[0148] This comparative example is the same as Example 1 except that the compaction density of the negative electrode in Table 1 is 2.0 g / cc.

[0149] Comparative Example 3

[0150] This embodiment is the same as Embodiment 1 except that the ratio of the first cold pressing in step (2) is 100%.

[0151] Comparative Example 4

[0152] This comparative example is the same as Example 1 except that the ratio of the first cold pressing in step (2) is 40%.

[0153] Comparative Example 5

[0154] This embodiment is the same as Embodiment 1 except that the battery discharge environment temperature in Table 1 is -50°C.

[0155] Comparative Example 6

[0156] This embodiment is the same as Embodiment 1 except that the battery discharge rate in Table 1 is 30C.

[0157] Test Example 1

[0158] This experimental example evaluates the performance of the negative electrode sheets and cylindrical batteries of Examples 1 to 9 and Comparative Examples 1 to 6, wherein:

[0159] (I) The test items and detection methods of negative electrode sheets include:

[0160] 1. Pole hole impedance R, double layer capacitance Cdl: EIS test is performed after the symmetrical battery is placed in a constant temperature oven at 25℃ for 6 hours.

[0161] 2. Porosity Porosity calculated by density method: The true density TD (True Density, g / cc) of each component of the negative electrode coating (active material, conductive agent, binder, dispersant) is tested by a true density meter, and the porosity of the coating is calculated by the compaction density a (g / cc) of the electrode coating.

[0162]

[0163] 3. Pore tortuosity τ: τ = (Rion·S·ε·σ) / d, τ is the tortuosity; Rion is the ionic resistance; S is the electrode area; ε is the diaphragm porosity; σ is the electrolyte conductivity; d is the electrode thickness.

[0164] R=Rion·S.

[0165] 4. Silicon particle breakage rate: The negative electrode is subjected to CP-SEM testing, and the breakage rate of silicon particles in a certain area is counted using BSE imaging (silicon particles have higher brightness). The SEM imaging magnification is more than 500 times, and more than ten areas are selected.

[0166] (II) Battery performance test takes NCA88+graphite / silicon carbon cylindrical battery test as an example. For other types of batteries, the test step parameters need to be modified.

[0167] Battery performance test items include:

[0168] 1. First effect: Place the unformed cylindrical battery in a constant temperature oven at 25℃ for more than 8 hours and test it according to the following steps:

[0169] (1) Charge the cylindrical battery at a constant current of 0.1C to a cutoff of 4.2V, and charge it at a constant voltage of 0.01C to a cutoff, and let it stand for 10 minutes, and read the capacity value Ca1 at this time;

[0170] (2) Discharge the cylindrical battery at a constant current of 0.1C to a cutoff of 2.5V, and let it stand for 10 minutes. Read the capacity value Ca2 at this time.

[0171] Then the first effect FCE of the cylindrical battery = Ca2 / Ca1.

[0172] 2. Discharge rate capacity retention rate: Place the aged cylindrical battery in a 25℃ constant temperature oven for more than 8 hours and test it according to the following steps:

[0173] (1) Discharge the cylindrical battery at a constant current of 0.1C to a cutoff of 2.5V and let it stand for 10 minutes;

[0174] (2) Charge the cylindrical battery at a constant current of 0.1C to a cutoff of 4.2V, and charge it at a constant voltage of 0.01C to a cutoff, and let it stand for 10 minutes;

[0175] (3) Discharge the cylindrical battery at a constant current of 0.1C to a cutoff of 2.5V, and let it stand for 10 minutes. Read the capacity value Q1 at this time.

[0176] (4) Charge the battery at a constant current of 0.1C to 4.2V, and charge at a constant voltage of 0.01C to a cutoff, and let it stand for 5 minutes;

[0177] (5) Then place the battery at an ambient temperature T (-40 ~ 0 ° C) for more than 8 hours, discharge it at a constant current at a corresponding discharge rate (K ≥ 8C) until it reaches 1.5V, let it stand for 10 minutes, and read the capacity value Q2 at this time;

[0178] Discharge rate capacity retention ratio CR (Capacity Retention) = Q2 / Q1.

[0179] 3. Overpotential: The test method for different discharge rate data is the same as that for the discharge rate capacity retention rate. The difference η=V2-V1 between the voltage V1 at different rates K (K≥8C) and the 0.1C voltage V2 at the same de-lithiation capacity is calculated.

[0180] 4. Cycle performance: Place the aged cylindrical battery in a constant temperature oven at ambient temperature T (-40~0℃) for more than 8 hours and test it according to the following steps:

[0181] (1) Discharge the cylindrical battery at a constant current of 0.1C to a cutoff of 2.5V and let it stand for 10 minutes;

[0182] (2) Charge the cylindrical battery at a constant current of 0.1C to a cutoff of 4.2V, and charge it at a constant voltage of 0.01C to a cutoff, and let it stand for 10 minutes;

[0183] (3) Discharge the cylindrical battery at a constant current of 0.1C to a cutoff of 2.5V, let it stand for 10 minutes, and read the capacity value at this time;

[0184] (4) Charge the battery at a constant current of 1.0C to 4.2V, and charge at a constant voltage of 0.05C to a cutoff, and let it stand for 5 minutes;

[0185] (5) Discharge the battery at a constant current of 10C to 1.5V cutoff, and let it stand for 10 minutes;

[0186] (6) Repeat steps (4) and (5) 600 times;

[0187] (7) The cycle performance of the battery, i.e., the capacity retention rate, is obtained by the ratio of the 600th discharge capacity in steps (4) and (5) to the discharge capacity in step (3).

[0188] 5. Adiabatic temperature rise characteristics test: refer to GB / T36276-2023.

[0189] 6. Battery electrical safety performance test: overcharge / overdischarge performance test, refer to GB / T36276-2023.

[0190] (III) Examples 1 to 5 and Comparative Example 1 are implementation methods for setting the silicon content in the negative electrode coating. The performance comparison of Examples 1 to 5 and Comparative Example 1 is shown in Table 2.

[0191] Table 2 Comparison of silicon content performance of negative electrode coating

[0192]

[0193] According to the results in Table 2, through the performance comparison of Examples 1-5 and Comparative Example 1, the results show that under the same compaction and cold pressing ratio conditions, with the increase of silicon addition, the negative electrode plate pore impedance, capacitance value and silicon particle breakage rate show an increasing trend, the battery overpotential increases, and the cycle retention rate decreases.

[0194] Among them, the implementation methods of Examples 1 to 3 with a silicon content of 2 to 10% have the best effect, with a discharge capacity of 100% and a cycle capacity retention rate of more than 94%. When the silicon content reaches more than 10%, the battery performance deteriorates significantly. The tap density of silicon-carbon material is lower than that of graphite. As the silicon content increases, the cold pressing conditions required to compact to 1.6g / cc become more stringent (pressure, roller gap), the pole piece pore structure is destroyed, the silicon-carbon particles are severely broken and block the pores, the pore impedance increases, and the double-layer capacitance value increases significantly. In particular, when the silicon content reaches more than 30%, the cycle capacity retention rate is only 78%, which cannot meet the application requirements.

[0195] At the same time, since the solid-phase diffusion coefficient of lithium ions in silicon-carbon materials is very low, when the silicon addition reaches more than 10%, the solid-phase diffusion impedance and pore impedance of the negative electrode increase significantly, the battery overpotential increases significantly, and the discharge capacity retention rate decreases at low temperatures.

[0196] In addition, due to the high volume expansion rate of silicon materials during the cycle, the particles are broken to produce new interfaces, and then iterative film formation causes active lithium loss. As the amount of silicon added increases, the particle breakage rate of the negative electrode sheet cold pressing process increases, and coupled with the high silicon cycle expansion rate, the battery's cycle capacity retention rate is significantly reduced.

[0197] (IV) Examples 6 to 8 and Comparative Example 2 are implementations of setting the compaction density of the negative electrode coating on the basis of Example 1. The performance comparison of Examples 6 to 8 and Comparative Example 2 is shown in Table 3.

[0198] Table 3 Comparison of compaction density performance of negative electrode coating

[0199]

[0200] According to the results in Table 3, by comparing the performance of Examples 1 and 6-8 and Comparative Example 2, the results show that: under the same silicon addition amount and secondary cold pressing ratio, with the increase of compaction density, the negative electrode porosity decreases, the active particles are more severely broken, the lithium ion transmission channels are reduced and the paths are longer, so the pore impedance and pore tortuosity of the negative electrode increase significantly. The overpotential of the cylindrical battery is significantly improved, and the low-temperature discharge capacity is significantly reduced.

[0201] In addition, due to the increased compaction, the negative electrode particles are more severely broken, and the negative electrode is iteratively filmed during the battery cycle, and the cycle capacity retention rate decreases. When the compaction reaches 2.0g / cc, the negative electrode pore structure collapses severely, the pore impedance increases significantly, and the battery performance drops sharply.

[0202] (V) Examples 9 to 12 and Comparative Examples 3 and 4 are implementations of setting the negative electrode secondary cold pressing ratio based on Example 1. The performance comparison of Examples 9 to 12 and Comparative Examples 3 and 4 is shown in Table 4.

[0203] Table 4 Comparison of negative electrode secondary cold pressing ratio performance

[0204]

[0205]

[0206] According to the results in Table 4, by comparing the performance of Examples 1 and 9-12 and Comparative Examples 3-4, the results show that as the first cold pressing ratio decreases, the negative electrode pore impedance first decreases and then increases, which is closely related to the secondary cold pressing conditions. The milder the first and secondary cold pressing conditions, the more complete the negative electrode pore structure, the smaller the degree of particle crushing, the lower the risk of blocking the lithium ion transmission channel, the lower the pore impedance, the higher the first effect, and the better the low temperature performance, cycle performance and safety performance. When the second cold pressing ratio exceeds 50%, the cold pressing conditions of Comparative Example 4 are more stringent than those of Example 12, so the pore impedance is higher than that of Example 12, and the overpotential is higher.

[0207] Figure 4 This is a comparison chart of the 10C discharge capacity cycles of the lithium-ion cylindrical batteries of Example 1 and Comparative Example 3 provided in this test example.

[0208] Depend on Figure 4 It can be seen that when the first cold pressing ratio is 100% (Comparative Example 3), the pole piece structure is destroyed, the battery performance is seriously reduced, and it is difficult to meet the demand.

[0209] (VI) Examples 13 to 16 and Comparative Example 5 are implementations of setting the battery discharge ambient temperature based on Example 1. The performance comparison of Examples 13 to 16 and Comparative Example 5 is shown in Table 5.

[0210] Table 5 Comparison of test battery discharge environment temperature

[0211]

[0212]

[0213] According to the results in Table 5, by comparing the performance of Examples 1 and 13-16 and Comparative Example 5, the results show that as the ambient temperature decreases, the viscosity of the electrolyte increases and the conductivity decreases. When the temperature drops to -50°C, the overpotential increases significantly, and the low-temperature discharge capacity and cycle capacity retention rate decrease significantly.

[0214] (VII) Examples 17 to 19 and Comparative Example 6 are implementations of setting the battery discharge ambient temperature based on Example 1. The performance comparison of Examples 17 to 19 and Comparative Example 6 is shown in Table 6.

[0215] Table 6 Comparison of test battery discharge rates

[0216]

[0217] According to the results in Table 6, through the performance comparison of Examples 1 and 17 to 19 and Comparative Example 6, the results show that: as the discharge rate increases, the overpotential increases significantly, and the low-temperature discharge capacity shows a downward trend. Due to the depolarization effect of the battery discharge temperature rise, the discharge rate reaches 20C, and the low-temperature discharge capacity still reaches 81%. When the discharge rate reaches 30C, the overpotential is too large, the temperature accumulation effect is insufficient, and the discharge capacity drops sharply to only 60%.

[0218] In summary, the present lithium-ion cylindrical battery and preparation method regulate the pore structure of the high-silicon negative electrode sheet through the negative electrode formula design (silicon content) and secondary cold pressing, reduce the negative electrode pore blocking phenomenon, reduce the pore impedance and pore tortuosity, improve the negative electrode lithium deintercalation kinetics, improve the cylindrical battery rate performance, and improve the low-temperature energy release of the battery. In addition, the present method can effectively improve the high-silicon negative electrode sheet particle breakage, reduce the formation of new interfaces during the cold pressing stage of the electrode sheet, reduce the consumption of active lithium, and improve the first efficiency and cycle performance of the whole battery. In addition, the negative electrode formula design (silicon content) and secondary cold pressing can improve the high-silicon negative electrode sheet particle breakage, reduce the formation of new interfaces during the cold pressing stage of the electrode sheet, reduce the occurrence of negative electrode side reactions, and improve thermal stability and electrochemical stability.

[0219] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A lithium-ion cylindrical battery, comprising a shell, a cylindrical core located in the shell, and an electrolyte, wherein the cylindrical core is wound by a positive electrode sheet, a negative electrode sheet, and a separator therebetween, characterized in that: The preparation method of the negative electrode sheet includes: Providing a negative electrode current collector, coating a negative electrode active slurry on the negative electrode current collector and drying it to obtain a negative electrode active coating, and then obtaining a negative electrode sheet through secondary cold pressing and slitting; The mass fraction of silicon in the negative electrode active coating is 2-30%, preferably 2-10%.

2. The lithium-ion cylindrical battery according to claim 1, characterized in that: The target compaction density of the secondary cold pressing is a, the compaction density of the negative electrode sheet coating before cold pressing is b, the ratio of the first cold pressing is c, and the compaction density after the first cold pressing is e, then e = b+(a - b)·c; Wherein: the target compaction density a of the secondary cold pressing is 1.2 g / cc ≤ a ≤ 1.8 g / cc, the compaction density b before cold pressing is 0.1 g / cc < b < 1.8 g / cc and b < a, and the ratio c of the first cold pressing is 0.5 ≤ c ≤ 0.

9.

3. The lithium-ion cylindrical battery according to claim 1, characterized in that: The hole impedance R of the negative electrode sheet satisfies R0·c·e x+(a-1) ≤R≤R0·e x+(a-1) , R0 is a=1, c=1, x=2%, the hole impedance of the negative electrode sheet satisfies 0.1Ω·cm 2 <R0<100Ω·cm 2 ; Wherein: a is the target compaction density of the secondary cold pressing, c is the ratio of the first cold pressing, and x is the mass fraction of silicon in the negative electrode active coating.

4. The lithium-ion cylindrical battery according to claim 1, characterized in that: The double-layer capacitance value Cdl of the negative electrode sheet satisfies Cdl0≤Cdl≤Cdl0(1+c) x+(a-1) , Cdl0 is the double layer capacitance value when a=1, c=1, x=2%, satisfying 1.00×10 -05 F / cm 2 <Cdl0<1.00×10 -02 F / cm 2 ; Wherein: a is the target compaction density of the secondary cold pressing, c is the ratio of the first cold pressing, and x is the mass fraction of silicon in the negative electrode active coating.

5. The lithium-ion cylindrical battery according to claim 1, characterized in that: The crushing rate ρ of the silicon particles of the negative electrode sheet after cold pressing satisfies ρ0·c·(1+x) 2 ≤ρ≤ρ0·(a+x) 2 ,ρ0 is the crushing rate of silicon particles when a=1, c=1, x=2%, satisfying 0≤ρ0<20%; Wherein: a is the target compaction density of the secondary cold pressing, c is the ratio of the first cold pressing, and x is the mass fraction of silicon in the negative electrode active coating.

6. The lithium-ion cylindrical battery according to claim 1, characterized in that: During the discharge process of cylindrical batteries, the absolute value of overpotential ηV and temperature T℃ satisfy: 0≤η≤1.3+e -(T / 10+4) , the discharge interval of the overpotential η is 0 to 10% DOD.

7. The lithium-ion cylindrical battery according to claim 1, characterized in that: The negative electrode active coating includes at least two of a negative electrode active material, a conductive agent, a binder, and a dispersant.

8. The lithium-ion cylindrical battery according to claim 7, characterized in that: The negative electrode active material includes at least two or a combination of two or more of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-carbon material, silicon-oxygen material, and silicon-based alloy.

9. The lithium-ion cylindrical battery according to claim 1, characterized in that: The diameter of the lithium-ion cylindrical battery is 20-50 mm, and the height is 50-150 mm.

10. A method for preparing a lithium-ion cylindrical battery according to any one of claims 1 to 9, characterized in that: The preparation method includes: (A) Preparing a negative electrode: adding a negative electrode active material, a conductive agent, a binder, and a dispersant to a solvent to form a mixed dispersion liquid A to obtain a negative electrode active slurry; then coating the negative electrode active slurry on at least one side of the current collector, and drying to form a negative electrode active coating; then obtaining a negative electrode sheet through secondary cold pressing and slitting; Preferably, the mass ratio of the negative electrode active material, the conductive agent, the binder, and the dispersant is 85-99.8:0.1-5:0.1-5:0-5; The negative electrode active material, the conductive agent, the binder, and the dispersant in the mixed dispersion liquid A are solutes; Preferably, the mass ratio of the solvent to the solute in the mixed dispersion liquid A is 0.25-4:1; Preferably, the solid content of the negative electrode active slurry is 20-80%; (B) Preparing a positive electrode: adding a positive electrode active material, a conductive agent, a binder, and a dispersant to an organic solvent NMP to form a mixed dispersion liquid B to obtain a positive electrode active slurry; then coating the positive electrode active slurry on at least one side of the current collector, and drying to form a positive electrode active coating; then obtaining a positive electrode sheet through cold pressing and slitting; Preferably, the mass ratio of the positive electrode active material, the conductive agent, the binder, and the dispersant is 85-99.8:0.1-5:0.1-5:0-5; The positive electrode active material, the conductive agent, the binder, and the dispersant in the mixed dispersion liquid B are solutes; Preferably, the mass ratio of the organic solvent NMP to the solute in the mixed dispersion liquid B is 0.25-1.5:1; Preferably, the solid content of the positive electrode active slurry is 40-80%; (C) Assembling cylindrical batteries: Winding the negative electrode sheet, the positive electrode sheet and the separator together to form a battery core, welding the tabs of the battery core to the electrical connection sheet and then placing them into a shell, injecting electrolyte, sealing and forming, to obtain the lithium-ion cylindrical battery.

11. An electrical device, characterized in that: It comprises the lithium ion cylindrical battery according to any one of claims 1 to 9.